Gap Junctions Mediate Bystander Cell Death in Developing Retina - Cusato, Karen (J Neurosci, 2003)
During development of the retina, programmed cell death helps to establish the final size and distribution of various cell classes in distinct layers of the tissue. Here we show that dying cells in the developing ganglion and inner nuclear layers are clustered spatially and that gap junction inhibitors decrease the clustering of dying cells. To confirm the role of gap junctions in cell death, we induced targeted cell death via intracellular cytochrome c (Cc) and examined the induced cells and their neighbors for apoptotic morphology or caspase-3 cleavage. These studies indicate that bystander killing extends to coupled cells. Quantitative studies of bystander killing were performed by scrape-loading retinas with Cc in the presence of rhodamine dextran (RD; to identify Cc-loaded cells) and by counting pyknotic cells in cryosections. Although only 1.5% of control scrape-loaded cells (RD alone) showed apoptotic morphology, 97% of Cc scrape-loaded cells were pyknotic. Moreover, bystander killing extended to neighboring cells, not labeled with RD, and was reduced significantly by the gap junction inhibitors octanol and carbenoxolone. We hypothesize that dying cells in the retina generate a gap junction-permeant apoptotic signal that mediates bystander killing. This novel finding of naturally occurring bystander cell death may have important implications in the histogenesis and pathology of the nervous system.